2014
DOI: 10.1371/journal.pone.0103078
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Dementia in Patients Exposed to Nitrogen Dioxide and Carbon Monoxide: A Population-Based Retrospective Cohort Study

Abstract: BackgroundThe air pollution caused by vehicular emissions is associated with cognitive decline. However, the associations between the levels of nitrogen dioxide (NO2) and carbon monoxide (CO) exposure and dementia remain poorly defined and have been addressed in only a few previous studies.Materials and MethodsIn this study, we obtained data on 29547 people from the National Health Insurance Research Database (NHIRD) of Taiwan, including data on 1720 patients diagnosed with dementia between 2000 and 2010, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 41 publications
1
120
2
1
Order By: Relevance
“…29 Of the 29 citations we identified for full text review, 26,27,2955 18 published articles met our eligibility criteria. 26,27,29,30,33,34,36,3841,4547,49,50,53,54 We describe the features of these studies in Section 3.1 and discuss individual and aggregate study quality in Section 3.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Of the 29 citations we identified for full text review, 26,27,2955 18 published articles met our eligibility criteria. 26,27,29,30,33,34,36,3841,4547,49,50,53,54 We describe the features of these studies in Section 3.1 and discuss individual and aggregate study quality in Section 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…27,30,34,38,4547,49,50,54 or presence and/or severity of neuroimaging markers obtained from a single brain magnetic resonance imaging (MRI) assessment (N=2). 36,53 Two studies evaluated the association between air pollution and change in cognitive test scores over time, 26,49 four evaluated the association between air pollution and incident cognitive impairment or dementia, 29,33,39,41 and one used a time-series-like approach to link year-to-year fluctuations in air pollution with year-to-year variation in hospital admissions for dementia or Alzheimer’s disease dementia. 40 Even within broad study design groupings, there was significant heterogeneity in both the approach to cognitive assessment and choice of instrument.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the increased dementia risk in the Santiago Metropolitan Region may be related to air pollution, many aspects of which - nitrogen oxides, carbon monoxide, particulate matter (PM 10 and PM 2.5 ), and ozone - have been related to dementia risk [33,34,35]. There is further supporting evidence from another large metropolitan area: a recent study found a biomarker which has been proposed for Alzheimer's disease [36] (reduced cerebrospinal fluid levels of Aβ 1-42 ) in children from Mexico City who had been exposed to high levels of air pollution in utero and throughout their life compared to controls [37].…”
Section: Discussionmentioning
confidence: 99%
“…While there is insufficient data to date on the link between air pollution and dementia risk, there is some evidence high levels of air pollution is associated with greater cognitive impairment in older adults (106-108) and air pollution has been associated with AD neuropathology (108). …”
Section: The Role Of Biomarkers: Indicators Of Mechanismsmentioning
confidence: 99%